2005
DOI: 10.1080/08860220500243338
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Thyroid Disfunction, Thyroid Autoantibodies, and Renal Function

Abstract: Fifty-eight patients with thyroid dysfunction were included, comparing 27 healthy subjects to evaluate the relationship between thyroid autoimmunity, thyroid functional status, and renal function. Regardless of clinical status, hypothyroidism was defined as T3-T4upper limit of normal, and hyperthyroidism was defined as T3-T4>normal limits and TSH <0.1 mcU/mL. In all participants, serum antithyroperoxidase level, serum antithyroglobulin level, creatinine clearance (CC), and urinary albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 16 publications
3
29
0
Order By: Relevance
“…The underlying mechanisms for these changes in s-CysC have not been investigated, and GFR was not measured in either study. However, it is unlikely that changes in s-CysC are reflected by an actual change in GFR, since the hypothyroid and hyperthyroid states are well known to be associated with decreased and increased GFR, respectively [93][94][95]. The impact of thyroid hormones on CysC has not yet been investigated in children.…”
Section: Cystatin Cmentioning
confidence: 90%
“…The underlying mechanisms for these changes in s-CysC have not been investigated, and GFR was not measured in either study. However, it is unlikely that changes in s-CysC are reflected by an actual change in GFR, since the hypothyroid and hyperthyroid states are well known to be associated with decreased and increased GFR, respectively [93][94][95]. The impact of thyroid hormones on CysC has not yet been investigated in children.…”
Section: Cystatin Cmentioning
confidence: 90%
“…The GFR in hypothyroid patients is approximately one-third lower than that of the euthyroid individuals (Singer 2001). Suher et al (2005) showed that subjects with hypothyroidism are associated with increased urinary albumin excretion rate and decreased creatinine clearance. In corroboration with our findings, T 3 was reported to have beneficial effects on renal function in a diabetic patient with end-stage renal failure and severe hypothyroidism (van Welsem & Lobatto 2007).…”
Section: Discussionmentioning
confidence: 99%
“…First, hypothyroidism is associated with decreased renal perfusion, 3 which results from decreased cardiac output and circulating volume, impaired RAAS activity, and decreased atrial natriuretic peptide concentration. 20,22,23 Second, growth retardation in the parenchyma of the kidney, as described in mature rats with experimental hypothyroidism, can decrease glomerular surface area. 24 Third, filtrate overload caused by deficient sodium and water reabsorption in the proximal tubule could lead to adaptive preglomerular vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%